Salmonella typhimurium has two homologous but different umuDC operons: cloning of a new umuDC-like operon (samAB) present in a 60-megadalton cryptic plasmid of S. typhimurium. - Nohmi, T (1991)
Expression of the umuDC operon is required for UV and most chemical mutagenesis in Escherichia coli. The DNA which can restore UV mutability to a umuD44 strain and to a umuC122::Tn5 strain of E. coli has been cloned from Salmonella typhimurium TA1538. DNA sequence analysis indicated that the cloned DNA potentially encoded proteins with calculated molecular weights of 15,523 and 47,726 and was an analog of the E. coli umuDC operon. We have termed this cloned DNA the samAB (for Salmonella mutagenesis) operon and tentatively referred to the umuDC operon of S. typhimurium LT2 (C. M. Smith, W. H. Koch, S. B. Franklin, P. L. Foster, T. A. Cebula, and E. Eisenstadt, J. Bacteriol. 172:4964-4978, 1990; S. M. Thomas, H. M. Crowne, S. C. Pidsley, and S. G. Sedgwick, J. Bacteriol. 172:4979-4987, 1990) as the umuDCST operon. The samAB operon is 40% diverged from the umuDCST operon at the nucleotide level. Among five umuDC-like operons so far sequenced, i.e., the samAB, umuDCST, mucAB, impAB, and E. coli umuDC operons, the samAB operon shows the highest similarity to the impAB operon of TP110 plasmid while the umuDCST operon shows the highest similarity to the E. coli umuDC operon. Southern hybridization experiments indicated that (i) S. typhimurium LT2 and TA1538 had both the samAB and the umuDCST operons and (ii) the samAB operon was located in a 60-MDa cryptic plasmid. The umuDCST operon is present in the chromosome. The presence of the two homologous but different umuDC operons may be involved in the poor mutability of S. typhimurium by UV and chemical mutagens.